Auswirkung der COVID-19-Pandemie auf deutsche paralympische Athleten - Kubosch, E. J.; Meidl, V.; Bretthauer, B.; Busch, A.; Leonhart, R.; Dallmann, P.; Wrobel, N.; Hirschmüller, A. (Sport-Orthopädie - Sport-Traumatologie, 2021)
Background: The purpose of this study was to bring the impact of the COVID-19 pandemic on competitive sports of german para-athletes into focus. We aimed to identify special aspects of disabled athletes during the pandemic, and their mental health. Material and Methods: All german candidate athletes preparing for the Tokyo Summer Paralympic Games were asked to complete a questionnaire, which consisted of questions about sports participation, physical and mental health, and the occupational and personal impact of the COVID-19 pandemic. Results: A total of 109 athletes (52 men, 57 women, mean age 29.2 (±10.4) years) completed the questionnaire between May 17th and August 30th 2020. 70% of the athletes felt that organizing their training was difficult, two-thirds of the athletes trained less than before. Half of the participants worried about their own well-being, 25% about their career, only 8% about their finances. Conclusions: The COVID-19 pandemic has a huge impact on sports of elite para athletes. Many athletes worried about the social impact and half of the respondents were of the opinion that people with disabilities were specially affected by the COVID-19 pandemic.